Influence of leadership styles on job satisfaction in the higher education institutions of Somaliland - Mukhtaar Axmed Cumar; Befekadu Zeleke Kidane; Negassa Golga Dawit; Feyera Dinsa (Cogent Education)
This study explores the influence of leadership styles on job satisfaction among academic staff in higher education institutions (HEIs) in Somaliland. Using a quantitative explanatory survey design, data were collected from 266 academic staff members across six universities, with leadership styles assessed using the Path-Goal Leadership Questionnaire (PGTQ) and job satisfaction measured through the Minnesota Satisfaction Questionnaire (MSQ). The study’s findings reveal that achievement-oriented and supportive leadership styles (SLS) are the most significant predictors of job satisfaction across general, intrinsic, and extrinsic dimensions. Participative leadership enhances intrinsic job satisfaction (IJS) but has a mixed effect on extrinsic and general job satisfaction (GJS). Directive leadership, while positively influencing job satisfaction, has a lesser impact compared to other styles. The results underscore the importance of leadership that fosters achievement and provides support in enhancing job satisfaction among academic staff. These findings contribute valuable insights into the leadership dynamics within Somaliland’s higher education sector, emphasizing the need for tailored leadership approaches that align with the cultural and institutional context.